Effects of different drying methods on the grinding characteristics of Ximeng lignite - Zhu, Jie-Feng; Liu, Jian-Zhong; Wu, Jun-Hong; Cheng, Jun; Wang, Zhi-Hua; Zhou, Jun-Hu; Cen, Ke-Fa (Fuel (Guildford), 2015)
•Microwave drying has the most remarkable effect on lignite grindability.•Combined drying has no advantages in improving lignite grindability.•Moisture removal and physical structure damage improve lignite grindability.•Energy saving can be achieved when lignite is irradiated for a short period. Ximeng lignite (XL) was treated by using different drying methods, namely, conventional, microwave, and combination, to investigate their effects on the grinding characteristics of XL. The controlled mechanisms that improved the grindability of XL treated by different drying methods were analyzed with proximate analysis and scanning electron microscope. Results showed that the removal moisture and the physical structure damage induced by thermal stress or steam jet flow improved the grindability of treated XL. Microwave drying had the most remarkable effect on the grindability of XL. The increments in grindability of XL irradiated for 0.5 and 3min were 44.03% and 200.45%, respectively. Compared with conventional dying, combined drying simultaneously improved grindability of XL, and reduced energy consumption. However, combined drying reduced the effects of microwave drying on the increment in the grindability of XL. Drying treatment for a short period could not effectively increase the mass fraction of finely ground product unless drying time was properly prolonged. According to the economy evaluation at lab scale, treatment of XL by microwave drying for a short period improved the grindability of treated XL and achieved a maximum energy saving of around 10% after a long period of the grinding process.